2011
DOI: 10.1002/cssc.201100046
|View full text |Cite
|
Sign up to set email alerts
|

Fischer–Tropsch Synthesis on Hierarchically Structured Cobalt Nanoparticle/Carbon Nanofiber/Carbon Felt Composites

Abstract: The hierarchically structured carbon nanofibers (CNFs)/carbon felt composites, in which CNFs were directly grown on the surface of microfibers in carbon felt, forming a CNF layer on a micrometer range that completely covers the microfiber surfaces, were tested as a novel support material for cobalt nanoparticles in the highly exothermic Fischer-Tropsch (F-T) synthesis. A compact, fixed-bed reactor, made of disks of such composite materials, offered the advantages of improved heat and mass transfer, relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…[43][44][45] It is well known that FT synthesis is a strongly exothermic reaction and usually CO conversion has to be limited to < 50 %. [46] The efficient three-dimensional thermal conductive network in this new type of support can offer an advantage of improved heat transfer, which is important for the highly exothermic FT reaction. The comparison between Co/SiC and Co/Al 2 O 3 (Co content = 30 wt %) showed that at medium conversions (< 50 %) the two catalysts displayed similar C 5 + selectivities.…”
Section: Effort To Improve C 5 + Selectivitymentioning
confidence: 99%
“…[43][44][45] It is well known that FT synthesis is a strongly exothermic reaction and usually CO conversion has to be limited to < 50 %. [46] The efficient three-dimensional thermal conductive network in this new type of support can offer an advantage of improved heat transfer, which is important for the highly exothermic FT reaction. The comparison between Co/SiC and Co/Al 2 O 3 (Co content = 30 wt %) showed that at medium conversions (< 50 %) the two catalysts displayed similar C 5 + selectivities.…”
Section: Effort To Improve C 5 + Selectivitymentioning
confidence: 99%
“…Selection of the appropriate catalysts and carriers for the FT reaction should obey several rules: good thermal conductivity of the support, [114] relatively low pressure drop along the catalyst bed if used in fixed-bed reactors, [115] effective utilization of all active sites present on the nanoparticles at the macroscopic level, [116] and intrinsic porosity of the support that favors evacuation of the products along with satisfactory accessibility to the reactants. [118][119][120] Recently, a new hierarchical support based on the use of low surface area a-Al 2 O 3 , which was homogeneously covered by a layer of CNTs (Figure 5 A), was successfully prepared by Liu et al [116] The composite exhibited a relatively high and fully accessible surface (specific surface area of 76 m 2 g À1 ), in comparison to the original support, that is, 5 m 2 g À1 (Figure 5 B). Chin et al [117] explored FeCrAlY foam decorated with aligned multiwalled CNT arrays as a microchannel support, and then a Co-Re active phase was loaded on this hierarchical structure for subsequent FT synthesis evaluation.…”
Section: Hierarchically Structured Compositesmentioning
confidence: 99%
“…47 A compact, fixed-bed reactor, made of disks of such composite materials, offered the advantages of improved heat and mass transfer, relatively low pressure drop, and safe handling of immobilized CNFs. An efficient 3-D thermal conductive network in the composite provided a relatively uniform temperature profile, whereas the open structure of the CNF layer afforded almost 100% effectiveness for Co nanoparticles in the Fischer-Tropsch synthesis in a fixed-bed.…”
Section: Carbon Nanostructured Materials On Carbon Feltsmentioning
confidence: 99%
“…CNTs and CNFs layers were formed on metallic (mostly Ni), 2-11 carbon, 12,13 or SiC [14][15][16] foams, reticulated vitreous carbon foam (hairy foam), 17,18 fibrous/sintered metal filters, [19][20][21][22][23][24] carbon, 25 oxide (mostly cordierite) [26][27][28][29][30][31][32][33][34][35][36][37][38] or metallic 39 monoliths, or carbon/graphite felts [40][41][42][43][44][45][46][47][48][49][50][51][52] (Figure 10.3 and Table 10.1). This helps to keep diffusion distances short.…”
Section: Macroscopic Shaping Of Nanostructured Carbon Materials For Cmentioning
confidence: 99%